An analysis for S-shaped I-V characteristics of organic solar cells using lumped-parameter equivalent circuit model. (1st January 2019) - Yu, Fei; Huang, Gongyi; Lin, Wei; Xu, Chuanzhong
Highlights: A lumped-parameter equivalent circuit model of organic solar cells (OSCs) is proposed. The explicit solution to I - V equation set of the lumped-parameter model is derived. Our model is suitable to be compactly implemented into computer-aided-design simulations of photovoltaic applications. We verify the simulation results of our proposed model by using numerical iteration results the experimental data. We discuss about effects from fitting parameters on I - V characteristics of OSCs. Abstract: A lumped-parameter equivalent circuit model of organic solar cells (OSCs) is proposed to analyze the S-shaped current-voltage ( I - V ) characteristics and the explicit solution to I - V equation is derived so that this model is suitable to be compactly implemented for the simulations of photovoltaic applications. Comparing our explicit solutions with the method of least squares and the Newton-Raphson root-finding scheme, the simulations quantificationally reproduce the S-shaped I - V characteristics of OSCs especially for both linear- and exponential-like S-shaped kink in the third and first quadrants, respectively. Simultaneously, the simulations facilitate us to qualitatively analyze the S-shaped I - V characteristics of OSCs influenced by the different model parameters. Furthermore, we verify the simulation results of our proposed model by using the reconstructed experimental data. Good agreements indicate that such a model can be used to accurately predict the S-shaped I - V characteristics of OSCs and regarded as a serviceable tool implemented compactly into simulations of the wide photovoltaic applications.